Delay constraint supported overlay multicast routing protocol - WU Jia-gao; YANG Yin-ying; CHEN Yi-xin; YE Xiao-guo (Tongxin xuebao)
The degree and delay constrained routing problem in overlay multicast was studied, and a new overlay multicast routing protocol called delay bounded tree protocol （DBTP） was proposed. Adopted distributed and tree-first strategies, the protocol enabled members of a multicast group to self-organize into a sourced-based overlay multicast tree. DBTP used a new heuristic local optimum algorithm, which could make trade-off between delay and cost of the multicast tree by adjusting a heuristic parameter. The simulation result shows that DBTP can both achieve the admission rate of members highly under whether static or dynamic node model through choosing a proper value of the heuristic parameter.